Stronger effects of heterozygosity on survival in harsher environments. Issue 6 (16th December 2018) - Vincenzi, Simone; Jesenšek, Dušan; Garza, John C.; Crivelli, Alain J.
Abstract : The hypothesis that the effects of heterozygosity vary with environmental conditions was tested using six populations of marble trout Salmo marmoratus from western Slovenia as a model system. The hypotheses tested were: stronger effects of heterozygosity on survival in populations characterized by low average survival; no effects of heterozygosity on probability of surviving flash floods owing to their largely non‐selective effects across traits; stronger effects of heterozygosity on survival for fish born after floods than fish born before. A significant effect of heterozygosity on survival was found in populations characterized by low average survival. There were no effects of heterozygosity on probability of surviving flash floods, but in one population a positive correlation between heterozygosity and survival for fish born after the extreme events was found, probably because crowding in a small section of the stream caused more intense competition for resources.